Thermodynamic performance and creep life assessment comparing hydrogen- and jet-fueled turbofan aero engine - Osigwe, Emmanuel O.; Gad-Briggs, Arnold; Nikolaidis, Theoklis; Jafari, Soheil; Sethi, Vishal; Pilidis, Pericles (MDPI, 2021)
There is renewed interest in hydrogen as an alternative fuel for aero engines, due to their perceived environmental and performance benefits compared to jet fuel. This paper presents a cycle, thermal performance, energy and creep life assessment of hydrogen compared with jet fuel, using a turbofan aero engine. The turbofan cycle performance was simulated using a code developed by the authors that allows hydrogen and jet fuel to be selected as fuel input. The exergy assessment uses both conservations of energy and mass and the second law of thermodynamics to understand the impact of the fuels on the exergy destruction, exergy efficiency, waste factor ratio, environmental effect factor and sustainability index for a turbofan aero engine. Finally, the study looks at a top-level creep life assessment on the high-pressure turbine hot section influenced by the fuel heating values. This study shows performance (64% reduced fuel flow rate, better SFC) and more extended blade life (15% increase) benefits using liquefied hydrogen fuel, which corresponds with other literary work on the benefits of LH2 over jet fuel. This paper also highlights some drawbacks of hydrogen fuel based on previous research work, and gives recommendations for future work, aimed at maturing the hydrogen fuel concept in aviation.
Keywords: jet fuel; exergy; aero engine; creep life assessment; gas turbine performance; liquefied hydrogen